The impact of copper additive content on the synthesis of SiC from rice husks - Kieu Do Trung Kien; Huynh Ngoc Minh (Materials Research Express, 2025)
Silicon carbide is a compound that is usually synthesized by sintering silicon dioxide and carbon in an arc furnace at high temperatures. This method requires sophisticated technology and equipment, which restricts the widespread application of silicon carbide. As a result, researchers have turned to biomass materials for its synthesis, with rice husk being the primary source. However, the efficiency of synthesizing SiC from rice husks tends to be relatively low. This study investigates the effect of copper additives on the synthesis efficiency of SiC. A mixture of rice husks, silica gel, and copper was prepared in varying ratios and then sintered at 1100 °C in a CO _2 atmosphere to promote SiC formation. The SiC content, mineralogical composition, and microstructure of the products were analyzed using ISO 21068-2:2008, Fourier Transform Infrared Spectroscopy, x-ray Diffraction, Scanning Electron Microscopy, and Energy Dispersive x-ray Spectroscopy. The results indicate that a rice husks-to-copper ratio of 1:2 significantly improved SiC production. Despite the enhancement, copper introduced unwanted impurities into the final products. These impurities were successfully removed by washing the SiC with hydrofluoric acid, resulting in a SiC content of 76.25% by weight. The synthesized SiC exhibited both α -SiC and β -SiC allotropic forms, contributing to improved mechanical strength and heat resistance of the material.